Symmetrical Contralaterally Controlled Functional Electrical Stimulation Enhanced Cortical Activity and Synchronization of Stroke Survivors - Rui Xu; Haichao Zhang; Xinyu Zhao; Zhuoyue Zhao; Lin Meng; Dong Ming (IEEE Transactions on Neural Systems and Rehabilitation Engineering, 2023)
Contralaterally controlled functional electrical stimulation (CCFES) is a rehabilitation method whose efficacy has been proved in several randomized controlled trials. Symmetrical CCFES (S-CCFES) and asymmetrical CCFES (A-CCFES) are two basic strategies of CCFES. The cortical response can reflect the instant efficacy of CCFES. However, it is still unclear of the difference on cortical responses of these different strategies. Therefore, the aim of the study is to determine what cortical response CCFES may engage. Thirteen stroke survivors were recruited to complete three training sessions with S-CCFES, A-CCFES and unilateral functional electrical stimulation (U-FES), in which the affected arm was stimulated. The electroencephalogram (EEG) signals were recorded during the experiment. The event-related desynchronization (ERD) value of stimulation-induced EEG and phase synchronization index (PSI) for resting EEG were calculated and compared in different tasks. We found that S-CCFES induced significantly stronger ERD at affected MAI(motor area of interest) in alpha-rhythm (8–15Hz), which indicated stronger cortical activity. Meanwhile, S-CCFES also increased intensity of cortical synchronization within the affected hemisphere and between hemispheres, and the significantly increased PSI occurred in a wider area after S-CCFES. Our results suggested that S-CCFES could enhance cortical activity during stimulation and cortical synchronization after stimulation in stroke survivors. S-CCFES seems to have better prospects for stroke recovery.